POTENSI BAHAYA DI KAWASAN WISATA GUNUNG BROMO, RESORT TENGGER LAUT PASIR, TAMAN NASIONAL BROMO TENGGER SEMERU, JAWA TIMUR (Hazard Potential at Bromo Mountain Tourism Area, Tengger Laut Pasir Resort, Bromo Tengger Semeru National Park, West Java) - Eva Rachmawati; Nunung Khusnul Faizah; E.K.S. Harini Muntasib (Department of Forest Resources Conservation and Ecotourism - IPB University, 2007)
Hazard is something considered may cause accident, disaster, misery or losses, both in moral and material. According to causing factors, hazard may occur due to natural factor and human factor. Potential hazard in a tourism area should be identified in order to ensure visitor’s safety and security, and to ensure that the visitor will gain maximum satisfaction while undergoing tourism activities in the area. The objectives of the research are to identify potential hazard in Gunung Bromo Tourism Area (KWGB), particularly those occured due to natural factor. Research was implemented by conducting interview and questionaire dissemination toward the area manager, community around the area, and the visitor;conducting measurement on H2S gas content in the field, and; conducting direct observation in the field. The result showed that hazard potential due to natural cause which likely to occur in the KWGB were Gunung Bromo volcanic activity, gorge, erosion/slide, weather/temperature, fire, lightning/thunderbolt, wind and earthquake.Keywords: Hazard, tourism, Bromo Tengger Semeru National Park